Omicron: we must protect the health and wellbeing of the public health workforce. (20th December 2021) - Pinho-Gomes, Ana-Catarina; Allen, Alexander; Rae, Maggie; Ryder, Julian
Abstract : The Faculty of Public Health warn of fatigue and lack of recovery time as two important factors affecting the public health workforce